The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1984-70332021v21n1a8
|View full text |Cite
|
Sign up to set email alerts
|

Stability of potato clones resistant to potato virus Y under subtropical conditions

Abstract: Brazilian potato production is based on cultivars originating from the USA and Europe; however, these cultivars were developed under different environmental conditions than those found in Brazil. The aim of this study was to evaluate the adaptability and stability of 18 potato clones (MLG), developed by the Universidade Federal de Lavras, and four cultivars in six environments in the state of Minas Gerais, Brazil. The following traits were evaluated: marketable tuber yield (MTY), specific gravity (SG), and tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Higher specific gravity is desired in potatoes, especially in processing types, as it indicates higher dry matter in the tuber and less oil absorption in fried/processed products. The specific gravity of potatoes decreases with high-temperature stress ( Teixeira et al., 2015 ; Andrade et al., 2021 ; Fernandes Filho et al., 2021 ). Various studies indicate a drastic reduction in tuber dry matter when potatoes are grown above 20-25°C ( Levy and Veilleux, 2007 ; Aien et al., 2017 ; Kim and Lee, 2019 ; Obiero et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher specific gravity is desired in potatoes, especially in processing types, as it indicates higher dry matter in the tuber and less oil absorption in fried/processed products. The specific gravity of potatoes decreases with high-temperature stress ( Teixeira et al., 2015 ; Andrade et al., 2021 ; Fernandes Filho et al., 2021 ). Various studies indicate a drastic reduction in tuber dry matter when potatoes are grown above 20-25°C ( Levy and Veilleux, 2007 ; Aien et al., 2017 ; Kim and Lee, 2019 ; Obiero et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For AMMI analysis, the X axis is the axis of the trait and the Y axis, the PC1, is the axis of stability. For the GGE biplot, the GGE method, PC1 is related to the adaptability of the genotypes, and PC2 is linked to the stability [28,56]. The AMMI analysis (Figure S1a,b) for the trait of plant height revealed that the G7 (Population 1) was the most stable and desired genotype, since it was placed on the right part of the X axis (the axis of trait) and had a low PC1 value, followed by the G5 (Chaironia), G2 (Dolichi), G4 (Ypati 84), and G1 (Florina).…”
Section: Ammi and Gge Biplotsmentioning
confidence: 99%
“…Sensory attributes for French fries and chippers are better in potatoes with high specific gravity (high dry matter, high starch). Heat stress has been reported to decrease the specific gravity of potatoes (Teixeira et al, 2015;Andrade et al, 2021;Fernandes Filho et al, 2021). The decrease in specific gravity is regarded as a loss to the processors.…”
Section: Specific Gravitymentioning
confidence: 99%